Flame atomic absorption determination of ultra-trace zinc in environmental samples after pre-concentration by solid phase extraction - Payehghadr, Mahmood (European Journal of Chemistry, 2017)
A simple, reliable and rapid method for pre-concentration and determination of ultra-trace zinc using octadecyl silica membrane disk modified by a new Schiff base ligand, and flame atomic absorption spectrometry is presented. Various parameters including, pH of aqueous solution, flow rates, the amount of ligand and type of stripping solvents were optimized. The breakthrough volume is greater than 1000 mL with an enrichment factor of more than 200 and 120 ng/Ldetection limit. The capacity of the membrane disks modified by 8 mg of the ligand was found to be 260 µg of zinc. The effects of various cationic interferences on percent recovery of zinc ion were studied. The method was successfully applied for the determination of zinc ion in different samples, especially determination of ultra-trace amount of zinc in waters and plants.